Recovering Cholesky Factor in Smoothing and Mapping - Touchette, Sébastien (Université d'Ottawa / University of Ottawa, 2018)
Autonomous vehicles, from self driving cars to small sized unmanned aircraft, is a hotly contested market experiencing significant growth. As a result, fundamental concepts of autonomous vehicle navigation, such as simultaneous localisation and mapping (SLAM) are very active fields of research garnering significant interest in the drive to improve effectiveness. Traditionally, SLAM has been performed by filtering methods but several improvements have brought smoothing and mapping (SAM) based methods to the forefront of SLAM research. Although recent works have made such methods incremental, they retain some batch functionalities from their bundle-adjustment origins. More specifically, re-linearisation and column reordering still require the full re-computation of the solution. In this thesis, the problem of re-computation after column reordering is addressed. A novel method to reflect changes in ordering directly on the Cholesky factor, called Factor Recovery, is proposed. Under the assumption that changes to the ordering are small and localised, the proposed method can be executed faster than the re-computation of the Cholesky factor. To define each method’s optimal region of operation, a function estimating the computational cost of Factor Recovery is derived and compared with the known cost of Cholesky factorisation obtained using experimental data. Combining Factor Recovery and traditional Cholesky decomposition, the Hybrid Cholesky decomposition algorithm is proposed. This novel algorithm attempts to select the most efficient algorithm to compute the Cholesky factor based on an estimation of the work required. To obtain experimental results, the Hybrid Cholesky decomposition algorithm was integrated in the SLAM++ software and executed on popular datasets from the literature. The proposed method yields an average reduction of 1.9 % on the total execution time with reductions of up to 31 % obtained in certain situations. When considering only the time spend performing reordering and factorisation for batch steps, reductions of 18 % on average and up to 78 % in certain situations are observed.
Keywords: SAM; SLAM; Cholesky